Multielemental Analysis of Biodiesel by Dynamic Reaction Cell–Inductively Coupled Plasma-Mass Spectrometry. (12th October 2016) - Ling, Zhao-Xing; He, Yang-Ming; Wang, Ping-Ya; Zhou, Ying; Ahmad, Farooq; Zhao, Fang-Fang
ABSTRACT: A simple, rapid, and reliable method is reported for the determination of Mg, Ca, Cr, Mn, Fe, Ni, Cu, Zn, and Pb in biodiesel by inductively coupled plasma-mass spectrometry (ICP-MS). To overcome problems related to the organic matrix in the direct introduction of the samples, a new extraction approach was investigated. The method was based on emulsion breaking, in which metals were transferred from the biodiesel to an acidic aqueous phase after formation and breaking of a water–oil emulsion prepared by mixing biodiesel with aqueous Triton X-114 and HNO3 . The pretreatment conditions were studied in detail. The dynamic reaction cell mode was used for the determination of Mg, Ca, Cr, and Fe by ICP-MS to eliminate interferences. The limits of detection and quantification for Mg, Ca, Cr, Mn, Fe, Ni, Cu, Zn, and Pb were from 0.007835 to 0.1896 µg/L and 0.02612 to 0.6320 µg/L, respectively. This method was validated by comparison with a well-established strategy of sample dilution and fortification.